Optimization of Productive Zakat for MSME Development Through Green Economics Principles: A Case Study of YBM Brilian in Medan - Ar Rahmah, Rizka; Hakim, Andy; Habib Rangkuti, Hasnul; Latifa Sari, Nurul (Fakultas Ekonomi dan Bisnis Islam, 2024)
The study aims to investigate how YBM Brilian in Medan utilizes productive zakat to empower local MSMEs while maintaining sustainable practices. The study also examines the mechanisms employed to ensure accountability and environmental responsibility among the zakat recipients. This qualitative case study involves an in-depth analysis of YBM Brilian’s productive zakat program. Data was collected through interviews, observations, and document reviews from the YBM Brilian program in the Medan region, focusing on its impact on MSMEs, particularly in the livestock sector. The research analyzes how green economic principles are integrated into their operations, and the ways in which zakat recipients are supported to achieve sustainable business growth. The findings reveal that YBM Brilian optimizes productive zakat by targeting the livestock sector through village-based programs, where zakat is used to provide cattle and goats as capital to MSMEs.